Corrosion Mechanism and Countermeasures in Oil Refineries - Comprehensive Review: - Comprehensive Review- - Al_qasaab, Mohammed R.; Wafee Hammoud, Ghassan; Al-Naffakh, Jameel T. (Journal of Petroleum Research and Studies, 2023)
Due to the international economic growth reliance on petroleum, corrosion is a critical problem for refineries and it has attracted considerable attention in recent times. There is a plethora of knowledge on the prevention of corrosion in petroleum refineries, but it is distributed among several scholarly studies. Therefore, a comprehensive and current analysis of corrosion prevention in refineries is required. Corrosion issues at several refinery units are examined in this paper. In addition, the foundations of the corrosion issue and modern mitigation techniques, like refinery design, cathode safeguard, inhibitors, and covering protection, were investigated. Study concludes by pointing out knowledge gaps, collecting adequate data on refinery facility corrosion, and offering suggestions for future studies.